Pengaruh Reciprocal Teaching Terhadap Hasil Belajar Siswa Tematik Kelas 5 SDN Sukorejo 1 - Miftahul Jannah; M. Bambang Edi Siswanto (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2023)
This research aims to determine the effect of reciprocal teaching on thematic learning on the learning outcomes of 5th graders at SDN 1 SUKOREJO. In this case, it refers to the book with the theme 7 events in life, sub-theme 2, national events surrounding the proclamation of learning independence 1 . the problem in education is learning that is less active and boring with the assignment learning model so that students are less interested and ignore it. Therefore, as a teacher, you must innovate in providing learning models every day. One of the learning models that can turn the class on is one of the reciprocal teaching models. This research uses a quantitative research approach with a pre-experimental type of design. The subjects of this study were 25 5th grade students of SDN SUKOREJO 1. The instruments in this test were the basic pre-test and the final test using post-post tests. Checking the data in this investigation using investigative spellbinding and measurable inferential with the encouragement of the SPSS program (Factual Bundle For sociology). The results of the study were mastering students' abilities in thematic learning before using the reciprocal teaching model and after using the reciprocal teaching model. In this case, the research effect is quite large, equivalent to 0.000 < 0.05 with the aim that if H0 is rejected and H1 is recognized. Meanwhile , it means that in this study the reciprocal teaching learning model affects student learning outcomes in thematic learning theme 7 sub - theme 2 pb 1 class 5 SDN SUKOREJO 1.